The state of Benefit Realisation Management in Iceland : and how to move forward - Lára Böðvarsdóttir 1980- (2018)
Benefit Realisation management (BRM) has been around for almost forty years. It's often referred as “common sense but not common practice”. Its maturity is not high in organisations in the world but is increasing. BRM is all about realising what are the benefits firm want, where does it want to be in so many years time and work back to determine the required changes that are needed in order to reach that goal for the organization. The aim of this thesis was to investigate the state of BRM in Iceland. Qualitative research through interviews with five experts, all of whom have extensive experience in project management, was conducted. None of the participants had heard of the phrase Benefit Realization Management and so the interview focused on their organization´s project management process, alignment with strategic goals, and measurement of benefits. The results of the interviews have been presented by common themes and topics that emerged during the interview process. The organizations interviewed were also then benchmarked against a list of best practices that characterize mature BRM practice. Each company was given a score on how well they perform and the average of these scores are used to gauge the state of BRM in Iceland. The research results suggest three areas that Icelandic companies should focus on to develop a more mature BRM practice, 1) sustaining benefits through more advanced benefits assessment and monitoring benefits going forward, 2) identifying benefits based on BRM and portfolio project management theory and 3) aim to develop experience and knowledge in using soft metrics when measuring benefits.